2020
DOI: 10.5039/agraria.v15i3a8221
|View full text |Cite
|
Sign up to set email alerts
|

Cacti-associated rhizobacteria from Brazilian Caatinga biome induce maize growth promotion and alleviate abiotic stress

Abstract: The aim of this study was to isolate and characterize the culturable rhizobacteria associated with native cacti from Caatinga biome, testing their potential in plant growth promotion and abiotic stress tolerance. Bacterial isolates were examined for plant growth promotion traits and for in vitro abiotic stress tolerance. Promising isolates were 16S rRNA sequenced, tested under greenhouse conditions for plant growth promotion and induction of water deficit tolerance in maize plants. Analysis of variance was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In drylands (arid and semi-arid regions), the association of plants (both crops and native species) with stimulating rhizobacteria is important to the plant’s establishment and development, since in addition to providing nutrients and stimulating growth, these microbes also help plants cope with drought stress [ 5 , 6 , 7 , 8 ]. These bacteria could be used as inoculants in agriculture since biofertilizers with high concentrations of microorganisms act on the growth and development of plants, increasing crop production, preserving soil life, reducing production costs, without causing damage to water resources or emissions of pollutants, and acting upon soil bioremediation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In drylands (arid and semi-arid regions), the association of plants (both crops and native species) with stimulating rhizobacteria is important to the plant’s establishment and development, since in addition to providing nutrients and stimulating growth, these microbes also help plants cope with drought stress [ 5 , 6 , 7 , 8 ]. These bacteria could be used as inoculants in agriculture since biofertilizers with high concentrations of microorganisms act on the growth and development of plants, increasing crop production, preserving soil life, reducing production costs, without causing damage to water resources or emissions of pollutants, and acting upon soil bioremediation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…had a negative effect on maize plants subjected to a drying-wetting cycle in the soil. Likewise, Santos et al (190), working with cactiassociated PGPB from Brazilian Caatinga biome, found that the Bacillus sp. strains were able to increase the shoot dry weight of maize plants under water deficit.…”
Section: Plant Growth-promoting Bacteriamentioning
confidence: 93%
“…More recently, other Bacillus spp. from the cactus rhizosphere of Brazilian Caatinga showed the potential to promote maize growth under drought conditions ( Santos et al, 2020 ). These reports reveal cacti as an underexploited source of PGPB to crops in agricultural practices under drought conditions.…”
Section: Plant-associated Bacteria From the Caatinga Biome And Their mentioning
confidence: 99%
“…Plant-associated bacteria that positively influence plant growth and development are collectively known as plant growth-promoting bacteria (PGPB). Given the current climate change scenario and future predictions of an increase in arid lands ( Beck et al, 2018 ), the prospect of PGPB from semiarid and seasonally dry regions to enhance crop yield under stress conditions has been explored ( Kavamura et al, 2013a ; Marasco et al, 2013 ; Shrivastava and Kumar, 2015 ; Jochum et al, 2019 ; Selim et al, 2019 ; Andrade et al, 2020 ; Santana et al, 2020 ; Santos et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%